KEPENTINGAN INDONESIA MENGEKSPOR CPO KE CHINA PADA TAHUN 2018-2020 - Sutis Aulya; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Indonesia is the owner of the largest palm oil commodity in the world. This can be seen from the size of the plantation area and the export value of Indonesian palm oil which is increasing every year. Therefore, several countries entrust Indonesia as a producer of CPO as a derivative of palm oil.Cooperation in improving the economy is a national interest. This cooperation can be in the form of trade carried out by Indonesia to various countries. In this study, the authors collect data through literacy such as books, magazines, newspapers, journals, articles and web pages. This study uses a way of analyzing a reading to get an understanding that is in accordance with the research. The method used by the author in this study is a qualitative method. This method tends to analyze a problem by collecting data and information through books, newspapers, articles, journals, and other reading materials that can be used as sources of information.This research focuses on Indonesia's interest in exporting CPO to China in 2018-2020 which is an effort to stabilize and improve the Indonesian economy. This effort can be seen from the increase in CPO exports by improving the quality of palm oil and its processing in Indonesia, which will have a good effect on CPO exports to China. Besides being able to stabilize and improve the country's economy, this can also strengthen Indonesia's relations with China. Keywords: economy, palm oil, export